Comparing the effects of Mycozin and Clotrimazole 1% creams on vaginal candidiasis: a triple-blinded randomized controlled trial - Khadije Hajizadeh; Zahra Alivand; Vahideh Rahmani; Leila Mehrannia; Sanam Nami; Behrooz Shokouhi; Mojgan Mirghafourvand (Scientific Reports)
Abstract Clotrimazole 1% and Mycozin vaginal cream have been reported to be effective in relieving the symptoms of vulvovaginitis caused by Candida. The resistance to azole compounds, and the side effects of chemical drugs have been reported following azole therapy. It was hypothesized that Mycozin is at least as effective as Clotrimazole in treating vaginal candidiasis. This equivalent, triple-blinded, randomized clinical trial was conducted on 126 patients who complained of vaginal itching referred to Al-Zahra Teaching Hospital, Tabriz, Iran between September 2023 and May 2024. Participants were divided into two groups, i.e., Mycozin (n = 64) and Clotrimazole 1% (n = 62), using the block randomization method. The patient's complaints, clinical signs, the pH and culture of the secretions was recorded before and after treatment. The patient's improvement, level of satisfaction, and side effects were recorded. The data were analyzed using Pearson chi-square test, ANCOVA, and Mann–Whitney U test. There was no statistically significant difference between the two groups regarding the mean pH (Adjusted mean difference: 0.01; 95% Confidence Interval (CI): −0.20 to 0.21, P = 0.965), and microscopic evaluation (Odds Ratio (OR): 0.61; 95% CI; 0.28 to 1.36, P = 0.230). After the treatment the frequency of itching in the Clotrimazole group (N = 13; 22.0%) was lower than that of the Mycozin group (N = 26; 43.3%) (OR: 0.37; 95% CI: 0.17 to 0.82; P = 0.013). There was no statistically significant difference in other symptoms and signs before and after the treatment (P > 0.05). Also, there was no statistically significant difference between the two groups in the level of satisfaction (P = 0.056) and patient improvement (P = 0.074). The side effects of treatment with Mycozin and Clotrimazole were observed in eleven and five patients, respectively. Considering the efficacy of Mycozin vaginal cream in eliminating most of the symptoms and signs associated with vaginal candidiasis and its positive effect in negating the results of culture, it can be used as a suitable alternative in the treatment of vaginal candidiasis in patients interested in herbal medicines and resistant to azole compounds. Trial registration: Iranian Registry of Clinical Trials (IRCT): IRCT20120718010324N77. Date of registration: 20/05/2023; URL: https://irct.behdasht.gov.ir/user/trial/68718/view ; Date of first registration: 31/05/2023.